Comparison of eyfluke (Diplostomum spp.) infections of polymorphic whitefish (Coregonus lavaretus L.) populations in two sub-Arctic Norwegian lakes - Øie, Ida (UiT Norges arktiske universitet, 2018)
Abstract Parasites might be small, but they are very important elements in the ecosystems. Parasites may have a strong negative influence on their host, and some species might even manipulate their hosts. Parasites commonly have complex life cycles and may use multiple different hosts. This study has been conducted in two sub-arctic lakes in Northern Norway with polymorphic whitefish populations. Both lakes, Suohpatjávri and Stuorajávri consist of three whitefish (Coregonus lavaretus L.) morphs, the near-shore large sparsely-rakerd morph (LSR), the pelagic densely-rakered morph (DR) and the deep-water small sparsely-rakered morph (SSR). Comparisons of the infection of eyeflukes in two eye habitats, the retina and vitreous humor (VH), of all three morphs were conducted both within and between each of the two lakes. The eyefluke has a rather complex lifecycle, with both egg, two free-living larval stages and three different stages involving different hosts (snail, fish and bird). The results showed that there is a difference in eyefluke infection between the three whitefish morphs within both lakes, with a few exceptions. Further, the results showed a difference in eyefluke infection between the same morphs between the two lakes Suohpatjávri and Stuorajávri. Suohpatjarvi generally was more infected with eyeflukes than Stuorajávri for both eye habitats. I suspect that the large shallow areas in Suohpatjávri may favor the abundance of the intermediate host snails quite well, since the LSR morph was more infected with eyeflukes than the other two morphs. There was a difference in the eyefluke infection between the two eye habitats the retina and the VH. In fact, the overall highest infection of eyeflukes in the VH was found in whitefish from Suohpatjávri, while Stuorajávri had the overall highest infection of eyeflukes for the retina. The eyefluke infection did not differ as much between the DR and SSR morphs which could mean that either the cercariaes find their way down to the profundal zone, or the SSR morph is ...